Fintech Adoption Behavior Among University Students - Johny Budiman; Candy Candy; Della Febrianti; Herisna Rahmadani; Dinda Rafika Syahputri; Anastassia Joan Liu (MDP Student Conference, 2026)
This study aims to analyze the effects of perceived usefulness, government support, and digital financial literacy on behavioral intention and use behavior in the use of Financial Technology (FinTech) services among university students. Data were collected through a questionnaire from 214 student respondents and analyzed using the PLS-SEM method. The results indicate that perceived usefulness and digital financial literacy have a positive and significant effect on behavioral intention and use behavior, while government support has no significant effect, either directly or indirectly. Furthermore, behavioral intention is proven to mediate the effects of perceived usefulness and digital financial literacy on use behavior, but it does not mediate the effect of government support. These findings suggest that perceived usefulness and digital financial literacy are the main factors driving students’ use of FinTech services.